The Phenomenon of Posting Memes on Instagram (Study on Employees of PT. Bank BTPN MUR Bengkulu) - Tri Wahyuniarti (GAYAKU PUBLISHER, 2023)
Social media today has been able to become a new media phenomenon that is familiar to the Indonesian people, especially teenagers to adults. With the power of virtual social media characteristics, it often produces booming phenomena for social media users themselves. In this study, researchers are interested in examining the phenomenon of memes on Instagram social media. The type of research in this research is qualitative research. The informants in this study are employees of PT Bank BTPN MUR Bengkulu as Instagram users who post memes using meme photos on their Instagram accounts. Where women are considered more courageous in showing their expressions in front of the public. The results showed that there are three motives behind Instagram users in doing meme posting activities, namely the entertainment motive, the love motive, the soul expression motive. In addition, in interpreting the meme posting activities carried out by Instagram users, researchers found two main points, namely users feel cared for by followers and feel that they are providing information to followers. So it can be said that the meme phenomenon is one of the phenomena where users convey messages in a new form by combining verbal language with nonverbal communication (expression).